Effect of imagery on free-throw shooting in basketball extracurricular - Novriansyah Novriansyah; Djoko Pekik Irianto; Yurieke Nadiya Rahmat; Fitri Agung Nanda (Jurnal Keolahragaan, 2019)
The purpose of this study was to find out differences in influence between internal imagery training and external training imagery on the results of free-throw shooting in extracurricular bola basketball, It used an experimental method. The sample was selected by random sampling technique which comprised three schools, SMPN 1 Bantul, SMPN 3 Bantul, SMPN 3 Jetis with a total of 42 bola basketball extracurricular students. An instrument measured the shooting free throw test to measure the free throw from Arianto B. The data were then analyzed using a two-track analysis of variance (ANOVA) at a significant level of α = 0.05. The results show that there is a significant difference between internal and external imagery training on the results of free-throw extracurricular bola basketball, which is evident from the value sig = 0.010 0.05. External exercises imagery provides a better influence on the results of free shooting extracurricular bola basketball.